2012
DOI: 10.1088/1748-9326/7/4/045703
|View full text |Cite
|
Sign up to set email alerts
|

Simulated impacts of insect defoliation on forest carbon dynamics

Abstract: Many temperate and boreal forests are subject to insect epidemics. In the eastern US, over 41 million meters squared of tree basal area are thought to be at risk of gypsy moth defoliation. However, the decadal-to-century scale implications of defoliation events for ecosystem carbon dynamics are not well understood. In this study, the effects of defoliation intensity, periodicity and spatial pattern on the carbon cycle are investigated in a set of idealized model simulations.A mechanistic terrestrial biosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 33 publications
3
65
1
Order By: Relevance
“…GEP returned to pre-disturbance values soon after each disturbance, corresponding to the rapid recovery of leaf area at each stand [11,17,21,54,56]. Following the cessation of herbivory or other disturbances that damage foliage early in the growing season (including experimental defoliation), canopy and understory oak species typically produce a second flush of leaves driven by the reallocation of nonstructural stored carbon (NSC) [36,37,54,55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GEP returned to pre-disturbance values soon after each disturbance, corresponding to the rapid recovery of leaf area at each stand [11,17,21,54,56]. Following the cessation of herbivory or other disturbances that damage foliage early in the growing season (including experimental defoliation), canopy and understory oak species typically produce a second flush of leaves driven by the reallocation of nonstructural stored carbon (NSC) [36,37,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, predicting the impact of invasive insects on long-term forest C dynamics using process-based simulation models has been only partially successful. Although process-based models have accurately captured the effects of gypsy moth defoliation on tree biomass, stand species composition, and the dynamics of GEP and ANPP, they have generally underestimated the long-term reduction in NEP in forests of the PNR following disturbance [9][10][11]. For example, the Ecosystem Demography 2 Model parameterized for xeric hardwoods and conifers and to represent defoliation events and tree mortality at oak-dominated stands in the PNR over 200-year simulations indicated that defoliation intensity was linearly related to decreases in annual NEP, but also predicted that post-disturbance NEP exceeded 80 to 90 g C m −2 year −1 at all levels of defoliation [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have represented insect damage in DVLSMs or less comprehensive climate-driven terrestrial models (Randerson et al, 1996;Krinner et al, 2005;Seidl et al, 2008;Wolf et al, 2008;Albani et al, 2010;Schäfer et al, 2010;Edburg et al, 2011;Medvigy et al, 2012;Mikkelson et al, 2013b;Chen et al, 2015). To our knowledge, however, our study is the first to assess, over daily to centennial timescales, the impacts from insect damage on vegetation dynamics and the carbon, energy, and water cycles in an integrated way (see Sect.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of prescribed mortality due to mountain pine beetle (MPB; Dendroctonus ponderosae Hopkins) outbreaks in western US on coupled carbon-nitrogen dynamics (Edburg et al, 2011) and water and energy exchanges (Mikkelson et al, 2013b) have been studied in the Community Land Model (CLM) DVLSM. Medvigy et al (2012) used the Ecosystem Demography version 2 (ED2) DVLSM to simulate the impacts of defoliation by the gypsy moth (Lymantria dispar Linnaeus) on vegetation coexistence and carbon dynamics in the eastern US. Background herbivory or insect outbreaks have also been simulated in DGVMs and other climate-driven terrestrial models (Randerson et al, 1996;Seidl et al, 2008;Wolf et al, 2008;Albani et al, 2010;Schäfer et al, 2010;Chen et al, 2015) less comprehensive than DVLSMs.…”
Section: -S Landry Et Al: Ibis-mimmentioning
confidence: 99%